The influence of intrauterine growth retardation on cardiac function, left ventricular mass and superior vena cava return in newborns - Anindita Soetadji; Najib Advani; Asril Aminullah; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2011)
Background Low birth weight (LBW) in neonates is a problemÂ leading to high morbidity and mortality. Barker hypothesized thatÂ fetal cardiac remodeling during hypoxic conditions or maternalÂ underô€nutrition is a risk factor for coronary heart disease in theyoung. Early vascular changes may influence cardiac function andÂ newborns' cerebral blood flow.Objective The aim of this study was to detennine the effectsÂ of being small for gestational age (SGA) on newborns' cardiacÂ function, left ventricular (LV) mass and superior vena cavaÂ (SYC) return.Methods This crossô€sectional study was conducted in CiptoÂ Mangunkusumo Hospital from February to June 2008. LBW andÂ nonnal newborns who fulfilled the inclusion criteria were recruitedÂ as subjects. Maternal history, infant physical examination, and echocardiography were obtained Mthin 48 hours oflife to excludeÂ those with congenital heart disease, and assess cardiac functionÂ and SYC flow.Results Subjects were 21 preterm appropriate for gestationalÂ age (AGA), 19 SGA and 19 normal newborns. SGA newbornsÂ showed lower LV mass, stroke volume and cardiac output thanÂ normal newborns. However, these SGA parameters were notÂ different from preterm AGA babies. In additio n, LV mass indexÂ was sig nificantly different but no difference ofSVC return betweenÂ the three groups.Conclusion SGA newborns' LV function was lower than that ofÂ nonnal newborns, as low as pretenn AGA newborns. N onnal SVCÂ return was observed in the three groups. This finding may be dueÂ to a brainô€sparing effect to maintain sufficient cerebral blood flowin the fetus.